Assessment of peste des petits ruminants vaccine wastage along the vaccine supply chain in Mali - Ilboudo, Guy S.; Sow, Ahmadou; Sidibé, C.A.K.; Ouedraogo, L.; Knight-Jones, Theodore J.D.; Fomba, C.O.; Dione, Michel M. (Frontiers Media, 2025)
This study was carried out in six regions of Mali to assess peste des petits ruminants (PPR) vaccine wastage along the vaccine supply chain during the vaccination campaign of 2023. Multi-stage stratified sampling was used to select 107 actors involved in the vaccine supply chain, including private veterinarians (n = 75), public vaccinators (n = 19), regional veterinary officers (n = 12), and one senior veterinary officer at the central level. Vaccine actors operated across the dominant small ruminants (SR) production systems in Mali (pastoral, agropastoral, and peri-urban). The World Health Organization field guidelines for monitoring and reducing vaccine wastage was used as a basis for this study. Results show that a quarter of vaccine doses were wasted. The vaccine wastage rate was 24.3% in public sector and 25.4% in private sector with approximately 90% of wastage occurring at the final stage of delivery (veterinary posts, or private veterinarians). At upstream points in the vaccine supply chain, wastage was low in both private and public distribution channels (less than 1%). No statistically significant difference was observed between the public and private sectors in vaccine wastage rates across the different stages of the vaccine distribution chain. The biggest cause of wastage was vaccine being discarded due to denaturation (46.0 and 32.4%, respectively, for the private and public actors), as doses were not used within the short (1 h) time window between reconstitution in the field and use. Also wastage was high due to improper injection (33.8 and 45.6% in public and private sectors), vial breakage (11.2 and 11.1%), and reconstitution errors (7.4 and 8.8%). The massive loss due to denaturation highlights the need for building stronger cold chains along the vaccine supply chain. In hard to reach areas, where cold chain failure is more likely, a vaccine able to remain potent for a longer period before and after reconstitution such as thermotolerant vaccines would add value. Furthermore, capacity of field vaccinators should be enhanced through trainings on best practices regarding vaccination.